2016
DOI: 10.4149/neo_2016_418
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants and risk of prostate cancer using pathway analysis of a genome-wide association study

Abstract: This study explored candidate causal single nucleotide polymorphisms (SNPs) to clarify the biological mechanism of prostate cancer (PCa). Identify candidate Causal SNPs and Pathways (ICSNPathway) analysis was applied using a PCa genome-wide association study (GWAS) dataset that included 473,736 SNPs in 1151 cases of PCa and 1156 controls of European ancestry. Five candidate causal SNPs, three candidate causal genes, and two candidate causal pathways were identified using integrating linkage disequilibrium anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…30 Also, a polymorphism in the KCNJ4 gene, which encodes another potassium channel, is associated with prostate cancer. 4 The research on membrane channels and transporters in cancer is still in the initial phase and can fill more gaps in the years to come.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Also, a polymorphism in the KCNJ4 gene, which encodes another potassium channel, is associated with prostate cancer. 4 The research on membrane channels and transporters in cancer is still in the initial phase and can fill more gaps in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 More recently, the nature and function of specific ion channels have been suggested to be involved in tumor development and progression. [3][4][5][6][7][8] Moreover, elevated levels of potassium and lowered levels of sodium have been found in patients with various types of cancer, 3,[9][10][11] probably due to oxidative damage 12 or cancer cell lysis. 13,14 Thus, extracellular electrolyte concentration may be linked to the diagnosis of cancer, either because the electrolyte composition may facilitate cancer development or result from an ongoing undetected cancer disease.…”
Section: Introductionmentioning
confidence: 99%
“…Second, CHRNA5 – CHRNA3 – CHRNB4 within chromosome 15q25.1 has been documented to modify some pathways of gated channel activity and ion channel activity, and therefore to play a crucial role in leading to and maintaining malignant phenotypes 43 . Finally, the majority of genes which were chosen as the significant or selected genes in the current GWAS pathway analyses, such as KCNJ4 44 , CACNB2 45 , and SLC14A 46 , have been reported to be involved in cancer etiology and development. In addition, our finding that genes from our susceptibility transporter activity GO terms jointly affected the chromosome 15q25.1-related lung cancer risk also supported the hypothesis that these pathways were implicated in the mechanisms of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NEIL3 also serves important roles in cancer ( 18 ). For example, Kim et al ( 19 ) reported that polymorphisms in NEIL3 increased the risk of prostate cancer. In glioblastoma, loss of NEIL3 increased replication-associated double strand breaks in DNA strands ( 20 ).…”
Section: Introductionmentioning
confidence: 99%